Mendorong Pertumbuhan Sikap Kerja Sama dan Tanggungjawab Melalui Kegiatan Piket Kelas Dalam Memelihara Lingkungan di Sekolah Dasar - Azizah, Wafiq Nur; Pranadita, Devy Herlina; Mitsaini, Fatimah; Kurniawati, Wahyu; Husna, Anisya Al (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to foster the growth of cooperation and responsibility through classroom cleaning activities in maintaining the environment at elementary schools. The method used in this study is a subjective qualitative approach, where data were obtained through participatory observation, in-depth interviews with teachers and students, and document analysis. The participants of the study were fifth-grade students. The results of the study indicate that classroom cleaning activities significantly contribute to the enhancement of students' cooperation and responsibility. During cleaning activities, students learn to work together with classmates in completing cleaning tasks and maintaining school facilities. They also show increased responsibility towards the cleanliness of their classroom and school environment. Teachers reported that students involved in cleaning activities exhibited positive changes in social interactions and increased awareness of school cleanliness. This study concludes that classroom cleaning activities are an effective way to instill cooperation and responsibility among elementary school students. The recommendations are for schools to sustain and develop classroom cleaning programs as part of character education curricula. Additionally, active participation of teachers in supervising and providing feedback during cleaning activities is crucial to maximize the benefits for students